Body Image Dissatisfaction and Its Associated Factors among Female Students at Sultan Qaboos University, Oman: A Cross-sectional Study - Safiya Al-Busaidi; Tamadhir Al-Mahrouqi; Sahar Al-Omrani; Faiza Al-Hajri; Azza Al-Salahi; Sachin Jose; Samir Al-Adawi (Saudi Journal of Medicine and Medical Sciences)
Background: Students worldwide have increasingly been reported to be strongly preoccupied with body image dissatisfaction (BID). Objective: To explore the prevalence of BID among female tertiary education students in Oman as well as to examine the relationship between sociodemographic variables, social media use, and BID expression. Materials and Methods: This cross-sectional survey study was conducted between January 1, 2022, and March 31, 2022, and included female undergraduate students from Sultan Qaboos University, Oman. The Arabic-validated self-administered questionnaires of Body Shape Questionnaire-34 and the Social Media Addiction Scale were used to elicit data. Results: A total of 463 students were included (mean age: 21.5 ± 3 years; single: 90.9% unmarried). Of these, 17.9% reported BID (95% CI: 14.54–21.73%). In the multivariate analysis, significant correlations were observed between BID and the subscales of social media addiction: time displacement (OR: 1.353; P = 0.001), compulsive tendencies (OR: 1.424; P = 0.001), and social consequences (OR: 1.200; P = 0.013). In addition, compared with respondents who had a normal BMI, the risk of BID was eight-fold higher among those who were overweight (OR = 8.514, 95% CI= 4.059-17.858; P <0.001) and 25 times higher among those who were obese (OR = 25.697, 95% CI = 8.266-79.886; P <0.001). Conclusions: This study found that about one-fifth of undergraduate female students from Oman experienced body image dissatisfaction, with higher prevalence among those who are overweight or obese. Significant associations were found between BID and social media use. These findings highlight the need for targeted interventions and awareness programs to address body image concerns and mitigate the impact of social media on student mental health.